View of the veranda depicting an arched door - Mumbai Archive Project (Jio Institute, 2024)
After decades of neglect, the building underwent a facelift, thanks to a collective effort by community members of Deussua. During the restoration, some material and structural changes were made to the century-old building. The original wooden flooring was replaced by marble flooring, and metal grilles were added to the windows. Even post-restoration, there is an overall sense of dilapidation and ageing, as evident from the peeled plaster on the walls of the veranda.